P595 Clinical effectiveness of golimumab: Interim analysis of the observational study of patients with ulcerative colitis on golimumab in the Swedish National Quality Registry for IBD–GO-SWIBREG. (16th January 2018) - Eriksson, C; Bergemalm, D; Vigren, L; Nilsson, L; Visuri, I; Hjortswang, H; Udumyan, R; Almer, S; Seddighzadeh, M; Hertervig, E; Karlén, P; Strid, H; et al.
Abstract: Background: Clinical trials may not appropriately reflect everyday clinical practice. Therefore, we aimed to assess the clinical effectiveness of golimumab in a real-world cohort. Methods: This is a prospective, observational, multi-centre cohort study. Eligible patients had an established diagnosis of ulcerative colitis, moderate-to-severe disease activity, defined as a Mayo endoscopic subscore ≥2 and initiated golimumab from 1 June 2014. All patients provided written consent. Clinical characteristics, treatment, clinical, biochemical, endoscopic activity and quality of life measures were recorded at baseline and prospectively, using an electronic Case Record Form, integrated with the Swedish National Quality Registry for IBD (SWIBREG). Primary objective was clinical effectiveness at 12 and 52 weeks, i.e. clinical response (defined as a decrease in Mayo score by ≥3 points or 30% from baseline) and remission (defined as a score of ≤2 with no individual subscores >1). Continuous data are presented as median (interquartile range). Differences between baseline and follow-up were assessed by Wilcoxon-signed rank test. Data from the 12-week induction part are presented. Results: Fifty patients were included, by 15/09/2017. At study entry, 24 of 50 (48%) were on concomitant treatment with immunomodulators, 16 of 50 (32%) on oral corticosteroids and 27 of 50 (54%) on 5-ASA. In total, 35 of 50 (70%) had previously been exposed to at least one TNF-antagonist (Table 1). At 12 weeks, 37 of 50 (74%) were still on treatment with golimumab (Figure 1). Of the patients continuing golimumab until Week 12, 8 (22%) were in clinical remission and 13 (35%) had a clinical response. The median Mayo score decreased from 7 (6–10) at baseline to 5 (1–8) at 12 weeks ( p < 0.01). Consistently, median faecal calprotectin decreased from 710 (275–1850) µg/g to 390 (45–870) µg/g ( p = 0.02). Quality of life improved in golimumab treated patients, with a significant reduction of the overall short health scale (SHS) score ( p = 0.04). Conclusions: This cohort of golimumab treated patients represents a treatment-refractory group. Improvements in clinical and inflammatory activity as well as in quality of life can be achieved already at 12 weeks. Funding: The study was financially supported by MSD.